Morality as a complex self-developing system - Belyaeva, Elena V. (Journal of the Belarusian State University. Sociology, 2019)
Interpretation of morality as a complex self-developing system contains fruitful possibilities for ethical research, allows to build a pluralistic and at the same time holistic picture of the dynamics of morality. The unity of morality as a system is determined by the peculiarities of its normative-value structure and specific function. Solving the problem of the diversity of morality is possible due to the use of the systemic-synergetic principle of nonlinearity. It allows to justify the spontaneous formation of a number of self-sufficient systems of morality that fulfill universal functions; interpret the process of determining morality as polydetermination and self-determination; еxplain the relationship of the universal and historically concrete in morality; to implement a scenario approach in determining trends in the development of modern morality. As a result, the dynamics of morality is represented as a process of self-organization of individual and collective subjects of morality that need for community stabilization and the assertion of the self-worth of an individual through the development of normative-value structures.